E-ARCHIVE DOCUMENT INFORMATION SYSTEM (CASE STUDY OF SMP NEGERI 12 DUMOGA) - Tiara Gloriani Siwu; Benny Pinontoan; Rillya Arundaa (Faculty of Mathematics and Natural Sciences Sam Ratulangi University, 2023)
Document archive processing is currently growing fast but has not been maximized as in SMP Negeri 12 Dumoga, where the document archiving process is still carried out conventionally by storing physical files, which are increasing over time and require a large storage area and extra time to search for the required documents. For this reason, with the development of existing technology, school document archiving can be done through a website-based storage system. The purpose of building this system is to facilitate the educational institutions of SMP Negeri 12 Dumoga in storing and searching documents. In addition, it can minimize the loss of school documents when the documents increase more and more and accumulate. The system was built and developed using the prototype system development method, which is carried out in stages starting from communication, quick plan, modeling quick design, construction of prototype, deployment, delivery and feedback. The website-based archive system can display the number of general and important documents stored in the e-archive. This e-archiving system has four menus: General Documents, Important Documents, Categories, and User Pages. This system can make archiving documents easier for administrative staff at SMP Negeri 12 Dumoga. System development can be done by adding features for photo and video archives documenting activities at SMP Negeri 12 Dumoga and development as part of the school's main website.